Analisis Pembelajaran Blended pada Masa Pandemi terhadap Aktivitas Belajar Siswa Kelas II SD N 02 Wiradesa Pekalongan - Firda Rahmania Arisanty; Ferina Agustini; Fajar Cahyadi (STKIP Andi Matappa Pangkep, 2021)
Student learning activities that are less than optimal during online learning are the background of this research. State 02 Wiradesa Elementary School applies blended learning, purpose of this study was to find how the implementation of blended learning during the pandemic on the learning activities of class II students at State 02 Wiradesa Elementary School. This type of research is a qualitative, the data of this study were obtained from interviews, observations, questionnaires, and documentation results. The results showed that students' learning activities when blended learning were good, but the students' motor activities were not optimal because the learning carried out by the teacher did not invite students to do motor activities. In addition, teachers have not implemented TPACK (Technological Pedagogical Content Knowledge) when learning because teachers still use conventional methods and have not utilized technology on the grounds that school conditions don’t support it. The implementation of blended learning during the pandemic must still comply with the health protocol, namely 3M (wearing masks, washing hands, and maintaining distance). The school environment is also supportive by providing hand washing stations, distributing masks to students, and arranging seats when offline learning at school to keep their distance from each other.